The annual training periodization of 8 World Champions in Orienteering - Tonnessen, E.; Svendsen, I. S.; Rønnestad, B. R.; Hisdal, J.; Haugen, T. A.; Seiler, S. (International Journal of Sports Physiology and Performance, 2015)
One year of training data from 8 elite orienteers were divided into a transition phase (TP), general preparatory phase (GPP), specific preparatory phase (SPP), and competition phase (CP). Average weekly training volume and frequency, hours at different intensities (zones 1-3), cross-training, running, orienteering, interval training, continuous training, and competition were calculated. Training volume was higher in GPP than TP, SPP, and CP (14.9 vs 9.7, 11.5, and 10.6 h/wk, P < .05). Training frequency was higher in GPP than TP (10 vs 7.5 sessions/wk, P < .05). Zone 1 training was higher in GPP than TP, SPP, and CP (11.3 vs 7.1, 8.3, and 7.7 h/wk, P < .05). Zone 3 training was higher in SPP and CP than in TP and GPP (0.9 and 1.1 vs 1.6 and 1.5 h/ wk, P < .05). Cross-training was higher in GPP than SPP and CP (4.3 vs 0.8 h/wk, P < .05). Interval training was higher in GPP than TP, SPP, and CP (0.7 vs 0.3 h/wk, P < .05). High-intensity continuous training was higher in GPP than CP (0.9 vs 0.4 h/ wk, P < .05), while competition was higher in SPP and CP than in TP and GPP (1.3 and 1.5 vs 0.6 and 0.3 h/wk, P < .01). In conclusion, these champion endurance athletes achieved a progressive reduction in total training volume from GPP to CP via a shortening of each individual session while the number of training sessions remained unchanged. This decrease in training volume was primarily due to a reduction in the number of hours of low-intensity, non-sport-specific cross-training.